Simultaneous determination of ribonucleoside and deoxyribonucleoside triphosphates in biological samples by hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry - Kong, Ziqing (Nucleic Acids Res, 2018)
Information about the intracellular concentration of dNTPs and NTPs is important for studies of the mechanisms of DNA replication and repair, but the low concentration of dNTPs and their chemical similarity to NTPs present a challenge for their measurement. Here, we describe a new rapid and sensitive method utilizing hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry for the simultaneous determination of dNTPs and NTPs in biological samples. The developed method showed linearity (R(2) > 0.99) in wide concentration ranges and could accurately quantify dNTPs and NTPs at low pmol levels. The intra-day and inter-day precision were below 13%, and the relative recovery was between 92% and 108%. In comparison with other chromatographic methods, the current method has shorter analysis times and simpler sample pre-treatment steps, and it utilizes an ion-pair-free mobile phase that enhances mass-spectrometric detection. Using this method, we determined dNTP and NTP concentrations in actively dividing and quiescent mouse fibroblasts.